Dissention in Tafsīr Principles and its Impact on Tafsīr Tazkirah by ‘Allamah ‘Anāyat Allah al-Mashraqī (1888-1963) - Rizwan Rasheed; Maria Ashraf (MEI, 2023)
All disciplines of knowledge are regulated by certain principles, associated to particular branches of study. Holy Qur’ān, as an everlasting miracle contains injunctions and rulings to all facets of life for all ages. Tafsīr, literally ‘to explain’ is the explanation of Holy Qur’ān. To provide elucidation for better understanding, different kinds of Qur’ānic interpretation are being penned from early Islamic history. Principles of Tafsīr, as a separate academic field, developed in early centuries of Islamic History in different phases. Few Tafsīr principles are unanimously agreed upon among exegetes while other is not accepted by all. Thus, dissention in Tafsīr principles lead the interpreters to ponder in Qur’ān differently and bring valuable aspects of Qur’ānic teachings into light. This research paper briefly reviews the fundamental principles of Tafsīr and its impacts on Tafsīr Tazkirah by ‘Allamah ‘Anayat Allah al-Mashraqī (d.1963). Exegetes of Subcontinent have contributed significantly to Tafsīr Literature. In all interpretations, exegetes established and describe few principles which they did follow to interpret Holy Qur’ān. Exegeses in subcontinent can be classified in two major types, Tafsīr bi al-Riwāyah (explanation through sound transmissions), and Tafsīr bi al-Ra’ay (Interpretation by reasoning). Generally, the later one was not approved by mainstream Islamic theologian of subcontinent. Moreover, comparison and relevancy of Tafsīr Tazkirah to traditional Tafsīr, as well as, outlook of this modernist exegete, is also a prime concern of this research paper. By adopting qualitative methodology, findings would be concluded in the end.